The Influence of Transformational Leadership Based on Rato Marapu on Organizational Culture Impacts on Teacher Performance in Senior High Schools in Southwest Sumba Regency - Lede, Yohanes Umbu; Nusa, Silvester; Sene, Mikael; Kelen, Konradus Doni; Kami, Kanisius (Journal of Ecohumanism, 2024)
Teachers play an important role in realizing quality education, teacher performance is influenced by many factors. The purpose of the study was to investigate and explain the influence of Rato Marapu-based transformational leadership on organizational culture and its impact on teacher performance. The research design was quantitative ex-post facto using a survey approach. The subjects of the study were 726 high school teachers in Southwest Sumba Regency. While the respondents were 297 people determined using the proportional random sampling technique by the Morgan formula then confirmed with Warwick and Lininger. Data collection used a questionnaire with 5-choice closed questions. Data testing applied a structural equation model to the Partial Least Squares approach. The results of the study were; (1) Rato Marapu-based transformational leadership has a strong direct influence on organizational culture based on the T-Statistic test results, namely 3.662 and P-Values, namely 0.000 (2) Rato Marapu-based transformational leadership also has a stronger direct influence on teacher performance based on the T-Statistic test results, namely 4.778 and P-Values, namely 0.000 (3) organizational culture has the strongest direct influence on teacher performance based on the T-Statistic test results, namely 33.864 and P-Values, namely 0.000 (4) Rato Marapu-based transformational leadership also has an indirect influence through organizational culture that has an impact on teacher performance, as evidenced by the T-Statistic test results, namely 3.762 P-Values, namely 0.000. The conclusion is that Rato Marapu-based transformational leadership based on Rato Marapu and organizational culture are predictors that influence teacher performance.